Mitochondrial function and reactive oxygen species dynamics in Italian Mediterranean buffalo semen following cryopreservation and post-thaw incubation - Loddo, Giada; Gelain, Maria Elena; Gabai, Gianfranco; D'Andrea, Asia; Montanari, Elisabetta; Milani, Chiara; Giaretta, Elisa (Frontiers in Veterinary Science, 2025)
IntroductionThe current understanding of physiological parameters and redox balance in buffalo bull semen is limited and derived from various breeds. Moreover, the effects of cryopreservation in various buffalo breeds remain unclear.MethodsThis study aimed to investigate the relationships between physiological parameters and compare fresh (F) and frozen-thawed (T) semen in Italian Mediterranean buffalos (IMB; 7, bulls). Buffalo ejaculates were collected using an artificial vagina and cryopreserved using a standard protocol. Both F and T were analyzed by CASA and flow cytometry Semen parameters assessed included motility, viability (using PI or SG counterstains for each assay), acrosome integrity (PSA), mitochondrial membrane potential (JC1), mitochondrial integrity (MT), intracytoplasmic (DHE) and mitochondrial (MX) superoxide production, and other intracellular reactive oxygen species (CR). The T samples were assessed immediately after thawing (T0) and following 3 h incubation at 37°C (T3).ResultsResults showed significant correlations (p < 0.05) between total motility (TM) and progressive motility (PM) with mitochondrial membrane potential (MMP) and mitochondrial integrity (MI). The TM, PM, MI, and MMP positively correlated (p < 0.05) with total reactive oxygen species (ROS) production and negatively with superoxide production. Cryopreservation significantly decreased TM from 92.1 ± 5.66% to 72.61 ± 18.62% (p < 0.05), H2O2 production from 23.02 ± 7.42% to 11.49 ± 8.85% (p < 0.05), and MMP from 83.29 ± 11.20 to 56.98 ± 15.87% (p < 0.05). After 3 h incubation, T semen exhibited increased mitochondrial damage and superoxide production, with decreased total ROS production.DiscussionIn conclusion, cryopreservation and subsequent incubation significantly affect mitochondrial functions, which strongly correlate with sperm motility. A deeper understanding of sperm energy metabolism and its relationship with redox regulation could allow for the optimization of current assisted reproductive technologies (ART), as these factors play a crucial role in sperm viability, motility, and fertilization capacity, which are critical for optimizing outcomes in ART procedures.